Microfinance Institutions in India - Piyush Tiwari and S.M. Fahad
More than subsidies poor need access to credit. Absence of formal employment make them non `bankable'. This forces them to borrow from local moneylenders at exhorbitant interest rates. Many innovative institutional mechanisms have been developed across the world to enhance credit to poor even in the absence of formal mortgage. The present paper discusses conceptual framework of a microfinance institution in India. The successes and failures of various microfinance institutions around the world have been evaluated and lessons learnt have been incorporated in a model microfinance institutional mechanism for India.